Systematic Review Toward A Definition of Technological Leadership - M. Gananta; Prawitra Thalib; Fendy Suhariadi; Ian Firstian Aldhi; Elvia Rahmawati; Dwi Hardaningtyas (Dinasti Publisher, 2024)
This article has three interconnected objectives. Firstly, it reviews the recent history of technology leadership research to position the definitions used within the current historical context. Secondly, it compiles a list of definitions and summarizes them through content analysis, providing a comprehensive definition of technology leadership. Thirdly, it presents measurements of technology leadership within an organization. By conducting a systematic review, the study compiles definitions and measurements of technology leadership, emphasizing problem-solving, facilitation, human orientation, interpersonal skills, continuous innovation, organizational support, personal attributes, strategic foresight, and ethical practices. The research provides a comprehensive definition and practical tools for assessing technology leadership, serving as a crucial foundation for future research and organizational strategies.